2020
DOI: 10.1073/pnas.2007749117
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidasin-mediated bromine enrichment of basement membranes

Abstract: Bromine and peroxidasin (an extracellular peroxidase) are essential for generating sulfilimine cross-links between a methionine and a hydroxylysine within collagen IV, a basement membrane protein. The sulfilimine cross-links increase the structural integrity of basement membranes. The formation of sulfilimine cross-links depends on the ability of peroxidasin to use bromide and hydrogen peroxide substrates to produce hypobromous acid (HOBr). Once a sulfilimine cross-link is created, bromide is released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…Br-ASO accumulation was observed in endolysosomes of renal tubule cells. When the bromine scale was altered, it was possible to visualize bromine enrichment in the basement membranes of the kidney ( Supplementary Figure S13 ) ( 45 ). Basement membrane proteins are normally brominated by the HOBr generated by peroxidasin, a peroxidase within the extracellular matrix ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Br-ASO accumulation was observed in endolysosomes of renal tubule cells. When the bromine scale was altered, it was possible to visualize bromine enrichment in the basement membranes of the kidney ( Supplementary Figure S13 ) ( 45 ). Basement membrane proteins are normally brominated by the HOBr generated by peroxidasin, a peroxidase within the extracellular matrix ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…When the bromine scale was altered, it was possible to visualize bromine enrichment in the basement membranes of the kidney ( Supplementary Figure S13 ) ( 45 ). Basement membrane proteins are normally brominated by the HOBr generated by peroxidasin, a peroxidase within the extracellular matrix ( 45 ). Bromine enrichment in endolysosomes of renal tubule cells in Br-ASO–treated mice was ∼70-fold higher than in the basement membranes and ∼178-fold higher than bromine enrichment in endolysosomes of renal tubule cells from control mice that had not been treated with Br-ASO ( Supplementary Figure S13 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups, including ours, have demonstrated that the mammalian enzyme functions in trimers as it was initially suggested for the Drosophila homolog [9,10]. It was also recently described that the enzyme mediates the bromination of tyrosine residues but the physiological significance of this activity remains to be clarified [11,12].…”
Section: Introductionmentioning
confidence: 78%
“…[ 64,65 ] Under normal physiological conditions, these reactions seem to be benign and peroxidasin activity is required for crosslinking of collagen IV. [ 65–67 ] However, under pathological conditions, including diabetes, myeloperoxidase enzyme activity is upregulated. [ 68 ] Studies have demonstrated that hypohalous acids damage the ECM both in vitro and in animal models of diabetes.…”
Section: Discussionmentioning
confidence: 99%